2023
DOI: 10.3390/ijms24129971
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Left Heart Diseases: Pathophysiology, Hemodynamic Assessment and Therapeutic Management

Abstract: Pulmonary hypertension (PH) associated with left heart diseases (PH-LHD), also termed group 2 PH, represents the most common form of PH. It develops through the passive backward transmission of elevated left heart pressures in the setting of heart failure, either with preserved (HFpEF) or reduced (HFrEF) ejection fraction, which increases the pulsatile afterload of the right ventricle (RV) by reducing pulmonary artery (PA) compliance. In a subset of patients, progressive remodeling of the pulmonary circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 202 publications
0
3
0
Order By: Relevance
“…In the CHAMPION study, an implantable sensor called CardioMEMS™ was used and provided for the funding [10]. The study enrolled patients with symptomatic heart failure irrespective of left ventricular ejection fraction in 64 centers across the USA.…”
Section: Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CHAMPION study, an implantable sensor called CardioMEMS™ was used and provided for the funding [10]. The study enrolled patients with symptomatic heart failure irrespective of left ventricular ejection fraction in 64 centers across the USA.…”
Section: Trialsmentioning
confidence: 99%
“…The REDUCE LAP-HF II trial was a prospective randomized controlled trial with an intervention group treated with an interatrial shunt device. [10] 626 patients with heart failure with preserved ejection fraction with isolated post-capillary pulmonary hypertension were treated with the device or placebo for up to 24 months. The study showed no significant effects of the device on the primary composite outcomes, which included cardiovascular deaths.…”
Section: Trialsmentioning
confidence: 99%
“…They must therefore be aggressively countered. In cases of bi-ventricular failure, diuretics should also aim at reducing left atrial pressure in order to decrease RV pulsatile load [88,89].…”
Section: Preload and Volume Managementmentioning
confidence: 99%